2010
DOI: 10.1073/pnas.1004021107
|View full text |Cite
|
Sign up to set email alerts
|

Flecainide increases Kir2.1 currents by interacting with cysteine 311, decreasing the polyamine-induced rectification

Abstract: Both increase and decrease of cardiac inward rectifier current (I K1 ) are associated with severe cardiac arrhythmias. Flecainide, a widely used antiarrhythmic drug, exhibits ventricular proarrhythmic effects while effectively controlling ventricular arrhythmias associated with mutations in the gene encoding Kir2.1 channels that decrease I K1 (Andersen syndrome). Here we characterize the electrophysiological and molecular basis of the flecainide-induced increase of the current generated by Kir2.1 channels (I K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 24 publications
1
81
0
Order By: Relevance
“…Several reports have concluded that both heteromeric and homomeric assembly of Kir2.x channels are the basis of native I K1 [16][17][18]. We have previously observed the effects of zacopride on cells co-transfected with heteromers of Kir2.1/Kir2.2, Kir2.2/Kir2.3, or Kir2.1/Kir2.3 [19]. Our results showed that zacopride did not induce an effect on the inward or outward components of the heteromeric channels, Kir2.1/Kir2.2, Kir2.2/Kir2.3, or Kir2.1/Kir2.3 ( Figures 3D-F, respectively).…”
Section: Zacopride Activates Kir21 But Not Kir22 or Kirchannels In mentioning
confidence: 99%
“…Several reports have concluded that both heteromeric and homomeric assembly of Kir2.x channels are the basis of native I K1 [16][17][18]. We have previously observed the effects of zacopride on cells co-transfected with heteromers of Kir2.1/Kir2.2, Kir2.2/Kir2.3, or Kir2.1/Kir2.3 [19]. Our results showed that zacopride did not induce an effect on the inward or outward components of the heteromeric channels, Kir2.1/Kir2.2, Kir2.2/Kir2.3, or Kir2.1/Kir2.3 ( Figures 3D-F, respectively).…”
Section: Zacopride Activates Kir21 But Not Kir22 or Kirchannels In mentioning
confidence: 99%
“…Currents were recorded using the whole-cell patch-clamp technique (15,17,18,30). Series resistance was compensated manually using the compensation unit of the Axopatch amplifier; ≥80% compensation was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…HL-1 and Chinese hamster ovary cells were transiently transfected by using Lipofectamine 2000 and FuGENE X-tremeGENE, respectively, and cultured as described (15,17,18,30).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms at play have not been fully elucidated in RYR2 related syndromes since in the RYR2 R4496C+/− transgenic mouse blockade of Ca 2+ transients and sparks was not determined not to be the antiarrhythmic mechanism, but rather flecainide sodium channel blockade which was the primary target for effective arrhythmia suppression(22). An alternative mechanism is related to the observation that flecainide, via a cysteine reside at position 311, has been shown to decrease Kir2.1 channel affinity for intracellular polyamine blockade, which functionally results in an increase in outward current(23). This, in essence, corrects the effect that the R67Q mutation induces and, thus, flecainide’s clinical action may also be directed on Kir2.1 channels.…”
Section: Discussionmentioning
confidence: 99%